Comprehensive Flow Cytometric Characterization of Bronchoalveolar Lavage Cells Indicates Comparable Phenotypes Between Asthmatic and Healthy Horses But Functional Lymphocyte Differences - Gressler, A. Elisabeth; Lübke, Sabrina; Wagner, Bettina; Arnold, Corinna; Lohmann, Katharina L.; Schnabel, Christiane L. (Frontiers in Immunology, 2022)
Equine asthma (EA) is a highly relevant disease, estimated to affect up to 20% of all horses, and compares to human asthma. The pathogenesis of EA is most likely immune-mediated, yet incompletely understood. To study the immune response in the affected lower airways, mixed leukocytes were acquired through bronchoalveolar lavage (BAL) and the cell populations were analyzed on a single-cell basis by flow cytometry (FC). Samples of 38 horses grouped as respiratory healthy or affected by mild to moderate (mEA) or severe EA (sEA) according to their history, clinical signs, and BAL cytology were analyzed. Using FC, BAL cells and PBMC were comprehensively characterized by cell surface markers ex vivo. An increased percentage of DH24A+ polymorphonuclear cells, and decreased percentages of CD14+ macrophages were detected in BAL from horses with sEA compared to healthy horses or horses with mEA, while lymphocyte proportions were similar between all groups. Independently of EA, macrophages in BAL were CD14+CD16+, which contrasts the majority of CD14+CD16- classical monocytes in PBMC. Percentages of CD16-expressing BAL macrophages were reduced in BAL from horses with sEA compared to healthy horses. While PBMC lymphocytes predominantly contain CD4+ T cells, B cells and few CD8+ T cells, BAL lymphocytes comprised mainly CD8+ T cells, fewer CD4+ T cells and hardly any B cells. These lymphocyte subsets’ distributions were similar between all groups. After PMA/ionomycin stimulation in vitro, lymphocyte activation (CD154 and T helper cell cytokine expression) was analyzed in BAL cells of 26 of the horses and group differences were observed (p=0.01–0.11). Compared to healthy horses’ BAL, CD154+ lymphocytes from horses with mEA, and CD4+IL-17A+ lymphocytes from horses with sEA were increased in frequency. Activated CD4+ T helper cells were more frequent in asthmatics’ (mEA, sEA) compared to healthy horses’ PBMC lymphocytes. In summary, FC analysis of BAL cells identified increased polymorphonuclear cells frequencies in sEA as established, while macrophage percentages were mildly reduced, and lymphocyte populations remained unaffected by EA. Cytokine production differences of BAL lymphocytes from horses with sEA compared to healthy horses’ cells point towards a functional difference, namely increased local type 3 responses in sEA.